Patterns of convergence in the central nucleus of the inferior colliculus of the Mongolian gerbil: organization of inputs from the superior olivary complex in the low frequency representation - Cant, Nell B. (Frontiers in Neural Circuits, 2013)
Projections to the inferior colliculus from the lateral and medial superior olivary nuclei were studied in the gerbil (Meriones unguiculatus) with neuroanatomical tract-tracing methods. The terminal fields of projecting axons were labeled via anterograde transport of biotinylated dextran amine and were localized on series of horizontal sections through the inferior colliculus. In addition, to make the results easier to visualize in three dimensions and to facilitate comparisons among cases, the data were also reconstructed into the transverse plane. The results show that the terminal fields from the low frequency parts of the lateral and medial superior olivary nuclei are concentrated in a dorsal, lateral and rostral area that is referred to as the “pars lateralis” of the central nucleus by analogy with the cat. This region also receives substantial input from both the contralateral and ipsilateral cochlear nuclei (Cant and Benson, 2008) and presumably plays a major role in processing binaural, low frequency information. The basic pattern of organization in the gerbil inferior colliculus is similar to that of other rodents, although the low frequency part of the central nucleus in gerbils appears to be relatively greater than in the rat, consistent with differences in the audiograms of the two species.